2011
DOI: 10.1080/17461391.2011.606838
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and criterion validity of the Self‐Administered Physical Activity Checklist in Greek children

Abstract: The purpose of this study was to assess the testÁretest reliability and criterion validity the Self-Administered Physical Activity Checklist (SAPAC) translated into the Greek language. To evaluate reliability, 72 students (35 girls and 37 boys) of the fifth and sixth grade completed SAPAC on two separate occasions, two weeks apart. Internal consistency was determined with Cronbach alpha coefficient and testÁretest reliability with the intraclass correlation coefficient (ICC). To evaluate criterion validity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
0
10
0
12
Order By: Relevance
“…Children were asked to read the completed questionnaire twice and the researcher provided assistance as needed. We have previously reported this questionnaire to have moderate‐to‐good reliability ( r > 0.85, P < 0.001) and validity ( r = 0.31 to 0.37, P < 0.001) …”
Section: Methodsmentioning
confidence: 94%
“…Children were asked to read the completed questionnaire twice and the researcher provided assistance as needed. We have previously reported this questionnaire to have moderate‐to‐good reliability ( r > 0.85, P < 0.001) and validity ( r = 0.31 to 0.37, P < 0.001) …”
Section: Methodsmentioning
confidence: 94%
“…A Tabela 1 apresenta a descrição dos 26 estudos. A confiabilidade teste-reteste foi investigada em 20 9,[14][15][16][17][18][19][20][21][22][28][29][30][31][32][33][34][35][36][37] deles, a validade de critério em 25 9,14-19,21-24,28-41 e a consistência interna em 5 16,21,37,38,40 . Em nenhum dos estudos, foi investigada a responsividade dos questionários.…”
Section: Resultsunclassified
“…Em nenhum dos estudos, foi investigada a responsividade dos questionários. A maioria dos estudos foi realizada na Europa 9,16,20,23,24,31,[35][36][37]39,41 e apenas cinco 15,21,28,30,33 deles no Brasil. Nos artigos incluídos, foram analisados 36 questionários estruturados, sendo seis de nacionalidade brasileira 15,21,28,30,33 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…All physical activities in the SAPAC were calculated in terms of: (1) physical activity METs score (MVPA METs) (min of activity X MET value); (2) weighted activity MET score (weighted MVPA METs) (min of activity X MET value X intensity rating) and (3) minutes of moderate to vigorous physical activity (min of MVPA). A recent study in Greece has demonstrated acceptable validity, reliability, and internal consistency of the SAPAC in young children [18].…”
Section: Methodsmentioning
confidence: 99%